1998
DOI: 10.1080/00288233.1998.9513326
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of six phosphate rocks and single superphosphate as phosphate fertilisers for clover‐based pasture

Abstract: Six phosphate rocks (PRs), Sechura (SPR), North Carolina (NCPR), Egypt (EPR), Arad (APR), Zin (ZPR), and Nauru (NPR), were compared with single superphosphate (SSP) as annually applied P fertilisers for mown ryegrass/ white clover swards at two sites, in the central North Island (Te Kuiti) and southern South Island (Woodlands) of New Zealand over a period of three years. NPR was finely ground before application but the other PRs were applied as received and so differed considerably in particle size distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…Because of MAF's dual role in research and extension, through the Agricultural Research and Farm Advisory Divisions respectively, the "National Series" received more prominence than other RPR trials. However, other very significant research was also conducted during the 1980s, principally by researchers from Massey University and the MAF's Agricultural Research Division, such as that presented by various authors in the RPR-specific workshop hosted by Massey University's Fertilizer and Lime Research Centre (FLRC) edited by Syers & Gregg (1981), and followed by many more such as Gregg et al (1988), Korte (1988), Ledgard et al (1992), Loganathan et al (1995), Mackay et al (1982Mackay et al ( , 1984aMackay et al ( ,b, 1986, Mackay (1990), McBride (1992, Percival et al (1984), Perrott et al (1993Perrott et al ( , 1996, Rajan & Upsdell (1981), Rajan & Gillingham (1986), Rajan et al (1994), Rajan (2002), Saggar et al (1992aSaggar et al ( ,b, 1999, Sinclair et al (1998), Syers et al (1986). As well as providing additional RPR pasture production data, topics covered by these authors included comparisons of different RPRs, comparisons of PAPRs with SSP and RPR, the effects of earthworms on RPR dissolution, and soil chemistry studies including the development of the new resin P test, which became widely used by RPR users because it better reflected the P-supplying ability of RPR reserves built up in the soil (Saggar et al 1999).…”
Section: The "National Series" and Other Mown-plot Rpr Trials Of The ...mentioning
confidence: 99%
“…Because of MAF's dual role in research and extension, through the Agricultural Research and Farm Advisory Divisions respectively, the "National Series" received more prominence than other RPR trials. However, other very significant research was also conducted during the 1980s, principally by researchers from Massey University and the MAF's Agricultural Research Division, such as that presented by various authors in the RPR-specific workshop hosted by Massey University's Fertilizer and Lime Research Centre (FLRC) edited by Syers & Gregg (1981), and followed by many more such as Gregg et al (1988), Korte (1988), Ledgard et al (1992), Loganathan et al (1995), Mackay et al (1982Mackay et al ( , 1984aMackay et al ( ,b, 1986, Mackay (1990), McBride (1992, Percival et al (1984), Perrott et al (1993Perrott et al ( , 1996, Rajan & Upsdell (1981), Rajan & Gillingham (1986), Rajan et al (1994), Rajan (2002), Saggar et al (1992aSaggar et al ( ,b, 1999, Sinclair et al (1998), Syers et al (1986). As well as providing additional RPR pasture production data, topics covered by these authors included comparisons of different RPRs, comparisons of PAPRs with SSP and RPR, the effects of earthworms on RPR dissolution, and soil chemistry studies including the development of the new resin P test, which became widely used by RPR users because it better reflected the P-supplying ability of RPR reserves built up in the soil (Saggar et al 1999).…”
Section: The "National Series" and Other Mown-plot Rpr Trials Of The ...mentioning
confidence: 99%
“…[3] This conclusion was arrived at averaging values across four sites, which was necessitated because of either very small or lack of response to P application in these sites in the early years of the experiment, and because the statistical power was insufficient for individual rates. Comparing the effectiveness of six PRs relative to single superphosphate, Sinclair et al [4] reported that the PRs were lagging behind SSP on two individual sites. However, the study was limited to three years and there is a need to provide a more definitive result on the long-term effect of PR application on individual soil types.…”
Section: Introductionmentioning
confidence: 98%
“…The relationship between P fertiliser and pasture production has been found to be similar under grazing to that found under mowing, despite some differences in absolute pasture production between the two trial techniques (Morton et al 1995, Morton & Roberts 2001). In addition, research has been carried out to measure the effectiveness of RPRs compared with SSP, again with most trials running for 3Á6 years (Mackay 1990, Sinclair 1990, Sinclair et al 1993, Sinclair et al 1998.…”
mentioning
confidence: 99%